The View from my Window - Gregory P. Magarian (Washington University Law Review, 2018)
The experience of writing a book and then reading what some very smart and knowledgeable people have to say about the subject matter is humbling and a little dizzying. In Managed Speech: The Roberts Court’s First Amendment, I try to make some sense of the present Supreme Court’s decisions over the past decade about the First Amendment’s protections for free expression. The book argues that those decisions, taken as a whole, excessively constrain free speech within a particular managerial framework. Rather than helping speech to flourish in all its noisy, messy glory, the Roberts Court favors First Amendment claims from powerful institutional speakers while backing the government against more socially and politically marginal speakers. Corporate political spenders and commercial data miners exemplify the Roberts Court’s First Amendment winners, while peace activists and fringe religions exemplify its losers. The Roberts Court’s First Amendment priorities constitute the managed speech of my title. The book contrasts managed speech with a free speech model I call dynamic diversity, which seeks to protect the change-making capacity of free speech by maximizing the range of perspectives and participants in public debate. Managed Speech opens a window onto the Roberts Court’s First Amendment. This symposium affords me the privilege of looking out, from the constraints of my knowledge and imagination, to observe what some friends whose work I greatly admire see in the spaces that window reveals. The main part of this essay highlights and briefly discusses some of the insights that I have found most immediately stimulating and valuable from each contribution to the symposium. The final section indulges some soul-searching. Our society over the past two years has plunged into a state of political chaos and uncertainty that, for many of us, has brought an overwhelming sense of rapid, highly unappealing displacement. Is this really the right time for me, or any person of good will, to be loudly criticizing the Supreme Court’s penchant for stability and insisting that, instead, First Amendment law should prioritize political and social dynamism?
Keywords: Managed Speech; Roberts Court; First amendment; Institutional speakers; Free speech